Ghost chilli pepper: a flaming hot slice - Gogoi, Bina Buragohain; Gogoi, Prodyut Bijoy; Das, Manish (Indian Horticulture, 2019)
Hottest chilli in the world, locally known as Bhut Jolokia (vernacular meaning Bhut = ‘ghost’, Jolokia = ‘chilli’), ‘BihJolokia’ (meaning poison chilli) or ‘Naga Jolokia’ (named after the once ferocious ‘Naga’ warrior tribe of North East India) belongs to Capsicum chinense Jacq. This chilli is being grown popularly and consumed in different states namely Asom, Manipur, Nagaland and Mizoram since time immemorial. The spiciness, pungent principle, and fiery sensation are caused by a compound ‘capsaicin’ localized mainly in the placenta and flesh of fruits. It survives both cooking and freezing temperatures and dissolves in fat. Capsaicin is found only in chilli, is detectable by human taste buds to one part in one million. This powerful alkaloid is extracted from chilli as an oleoresin (thick oil). The oleoresin is refined into a white crystalline powder which is the pure capsaicin.